The historical archaeology of revolutionary war encampments of Washington's army - Sgarlata, Cosimo; Orr, David Gerald, 1942-; Morrison, Bethany A., 1969-; Starbuck, David R. (Florida scholarship online., 2019)
This edited volume presents archaeological and ethno-historic research concerning Washington's Army's encampments, trails, and support structures during the American Revolution. Important sites and preserves that the following chapters discuss include Valley Forge in Pennsylvania; Putnam Park and General Parson's Preserve in Redding, Connecticut; Morristown National Historic Park in New Jersey; and Rochambeau's marching trail through Connecticut. Topics pursued by contributors to the volume are the military discipline and training of soldiers; the routine activities of soldiers and officers; the special accomodations accommodations at George Washington's headquarters at Valley Forge; the layouts and organizations of encampments; the participation of African descendants, Native peoples, and women in the war; and the historic technology used by soldiers to construct their winter quarters.